KECOCOKAN CELEBRITY ENDORSER DENGAN CITRA MEREK - Endah Widati (Universitas Indraprasta PGRI, 2016)
Advertising is one of promotion mix which usually used by the companies to inform and persuasive the companies’ product. To make an interesting advertising and able to make the audiences aware of the product, many factors have to be considered. One factor is source message. Generally, companies use famous person such as artist, celebrity, athletes, etc., as message resources because it will catch the audience’s attention and increase the companies’ sales revenues. But have to be realized that using celebrity as an endorser will give both positive and negative impact. This study is a conceptual paper, aims to find how the fittest of celebrity endorser and its effect towards brand image of the product. This study finds that the fittest of celebrity endorser will give many positives result if the companies have clear brand image and choose appropriate celebrity. Keyword: celebrity endorser, brand image, endorsement, brand ambassador